Shock Wave Structure of One-Dimensional Hydro-Elastoplastic Riemann Problem with Elastic-Plastic-Fluid Phase Transition (Advances in Applied Mathematics and Mechanics, 2024)
In this work, the types of shock wave structure for hydro-elastoplastic modelunder compression are researched. The emphasis focuses on the theory of shock transition in the presence of elastic-plastic-fluid phase transition. As a result, in addition tothe classical three-wave structure, two new shock wave patterns are found with the increase of loading strength. Several numerical tests are presented to verify the existenceof the three types of wave structure.